PERTUMBUHAN TANAMAN CABAI (CAPSICUM ANNUUM L.) PADA PEMBERIAN TIGA JENIS PUPUK KANDANG DAN PUPUK PHONSKA - Maria G. M. Polii; Pemmy ., Tumewu; Beatrix ., Doodoh; Rinny ., Mamarimbing; Jeane S. M. Raintung (Universitas Sam Ratulangi, 2022)
This research was conducted to study the effect of the interaction between three types of manure and Phonska fertilizer on the growth of chili plants, as well as to obtain the type of manure and the dose of Phonska fertilizer in increasing chili growth. The treatments were arranged in a factorial randomized block design (3x4) with three replications. The first factor (A) is three types of manure, namely A1 = 10 tons / ha of cow manure, A2 = 10 tons / ha of goat manure, A3 = 10 tons / ha of chicken manure. The second factor (B) is the dose of Phonska fertilizer; namely: Bo = without Phonska; B1 = 100 kg Phonska /ha, B2 = 200 kg Phonska /ha, B3 = 300 kg Phonska /ha. All experiments were repeated three times to obtain 36 experimental units. The variables observed in the study were plant height and number of chilies. The results showed that goat and chicken manure gave the highest plant height, as well as the number of chilies. The best chili plant growth was at a dose of 10 tons/ha of goat manure and 10 tons/ha of chicken. At 100 kg/ha Phonska fertilizer gave the best chili growth. The lowest plant height and the least number of fruits were found in the treatment without Phonska fertilizer.